A hybrid form of retinopathy of prematurity. Issue 4 (17th November 2011) - Sanghi, Gaurav; Dogra, Mangat R; Dogra, Mohit; Katoch, Deeksha; Gupta, Amod
Abstract : Aims: To study a hybrid pattern of retinopathy of prematurity (ROP) demonstrating both ridge tissue (simulating staged ROP) and flat neovascularisation (simulating aggressive posterior retinopathy of prematurity (APROP)) in the same eye. Methods: Retrospective chart review from January 2006 to June 2010. We reviewed the retinal drawings and Retcam images for a hybrid pattern of ROP, that is, presence of ridge tissue (characteristic of staged ROP) along with flat neovascular syncytium (characteristic of APROP) in the same eye. Results: 28 eyes of 18 infants had hybrid characteristics. All eyes had severe plus disease, flat new vessels at the junction of the vascular and avascular retina and ridge tissue at variable locations. Three patterns were noted: I Ridge at the junction of vascular and avascular retina (14 (50%) eyes); II Ridge in the vascularised posterior retina (10 (35.71%) eyes); III Ill-defined ridge close to the optic disc, with mat-like fibrous proliferation into the vitreous (4 (14.29%) eyes). After confluent laser photocoagulation, we observed favourable outcome in 92.3% eyes with pattern I, 100% eyes with pattern II and 25% eyes with pattern III disease. Conclusion: Some eyes with ROP may have abnormal neovascularisation resembling both APROP and classical staged ROP. It is difficult to characterise these eyes according to the international classification of ROP. However, the presence of plus disease should serve as guide to treatment.